Patient Experiences of Seeking Specialized Mental Health Care in Norway: A Qualitative Study - Silje Sørum; Veronica Lockertsen; Sara Rivenes Lafontan (Journal of Primary Care & Community Health)
Background: Despite the increasing prevalence of mental health concerns in Norway, limited knowledge exists regarding how patients experience accessing specialized mental health services through primary care. General Practitioners (GPs) act as crucial gatekeepers, yet their interactions and referral practices significantly influence patients’ help-seeking trajectories. This study aims to explore patient perspectives on the role of GPs as gatekeepers to specialized mental health care, with a focus on communication, decision-making, and navigation challenges within the Norwegian healthcare system. Methods: An exploratory qualitative study was conducted involving semi-structured interviews with 13 adults (9 women and 4 men), aged 20 to 43 years, who had been referred to specialized mental healthcare in the past 2 years. Participants were recruited using a pragmatic, self-recruitment strategy via social media platforms, and community mental health services. Interviews were conducted between September and October 2021, transcribed verbatim, and analyzed thematically using Braun and Clarke’s 6-step reflexive thematic analysis. Results: Three main themes were generated: (1) “The critical role of GP acknowledgment”: participants felt deeply affected by whether their GP validated or dismissed their emotional distress; (2) “An arbitrary choice of treatment”: patients reported confusion due to insufficient guidance from GPs, inadequate available information, and perceived randomness in referral practices; and (3) “A degrading process”: participants described feeling powerless, frustrated, and personally responsible for their difficulties navigating the referral system, often exacerbating their mental health symptoms. Conclusion: Patients frequently experienced feeling unsupported and overwhelmed due to poor GP engagement, inadequate information, and complex referral procedures. Enhancing GP mental health literacy, providing decision-making aids, and creating a centralized digital referral platform could significantly improve patient experiences, reduce waiting times, and foster a more effective, equitable, and patient-centered mental health care system.